Tryptophan Silver Nanoparticles Synthesized by Photoreduction Method: Characterization and Determination of Bactericidal and Anti-Biofilm Activities on Resistant and Susceptible Bacteria. (February 2019) - Courrol, Daniella dos Santos; Lopes, Carla Regina Borges; Pereira, Camila Bueno Pacheco; Franzolin, Marcia Regina; Silva, Flávia Rodrigues de Oliveira; Courrol, Lilia Coronato
The high rates of antibiotics use in hospitals have resulted in a condition where multidrug-resistant pathogens have become a severe threat to the human health worldwide. Therefore, there is an increasing necessity to identify new antimicrobial agents that can inhibit the multidrug-resistant bacteria and biofilm formation. In this study, antibacterial and anti-biofilm activities of tryptophan silver nanoparticles (TrpAgNP) were investigated. The TrpAgNPs were synthesized by photoreduction method, and the influence of irradiation time and concentration of reagents were analyzed. The nanoparticles were characterized by transmission electron microscopy, Zeta Potential and (UV)-absorption spectra. The antibacterial activity of TrpAgNPs was tested for antibiotic-resistant and susceptible pathogens, Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli, Citrobacter freundii, Klebsiella pneumoniae, Salmonella typhimurium, and Pseudomonas aeruginosa, evaluating the influence of photoreduction parameters in bactericidal effect. The results have shown that TrpAgNPs solutions with lower tryptophan/silver nitrate (AgNO3 ) ratio and higher AgNO3 concentration have higher bactericidal action against bacteria with inhibition of ~100% in almost all studied bacterial strains. The antimicrobial activity of TrpAgNPs within biofilms generated under static conditions of antibiotic-resistant and susceptible strains of S. aureus, S. epidermidis, E. coli, K. pneumoniae, C. freundii, and P. aeruginosa was also investigated. The results showed that TrpAgNPs have an inhibitory effect against biofilm formation, exceeding 50% in the case of Gram-negative bacteria ( E. coli, K. pneumoniae, C. freundii, and P. aeruginosa —54.8% to 98.8%). For Gram-positive species, an inhibition of biofilm formation of 68.7% to 72.2 % was observed for S. aureus and 20.0% to 40.2% for S. epidermidis .